Enhancing the maintenance practice to improve guests’ satisfaction in the hotels industry / Cheong Peng Au-Yong, Pui Kei Hoh and Daniel Amos - Cheong, Peng Au-Yong; Pui, Kei Hoh; Amos, Daniel (UiTM Press, 2024)
Lack of maintenance could result in complaints from guests which could affect overall satisfaction and reputation of the hotel. Unfortunately, this issue remains where the majority of the complaints are from the tangible factor with guests complaining about hotel amenities. Therefore, this paper aims to propose effective maintenance practices for hotels to improve the satisfaction level of guests. Eight (8) factors that affect maintenance practice were identified through an extensive literature review. The study gathered survey data via thirty-three (33) questionnaires that were distributed to hotels ranging from three (3) to five (5) star hotels in Klang Valley and Ipoh and involved three (3) face-to-face interviews. Correlation analysis was performed to assess the relationship between maintenance factors and the satisfaction level of guests. The results revealed that three (3) factors were significantly correlated with the overall guests’ satisfaction. The perception of interviewees regarding the factors affecting maintenance practice further validates the survey findings. This paper implies the importance of maintenance operations to improve guests’ satisfaction as well as identifying factors that lead to positive bias toward effective hotel maintenance management.